2021
DOI: 10.1108/jet-08-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and usage of mHealth technologies amid COVID-19 pandemic in a developing country: the UTAUT combined with situational constraint and health consciousness

Abstract: Purpose The COVID-19 pandemic has created a devastating effect on public health. As “social distance” is a highly effective preventive measure of this pandemic, close contact between a patient and physician is strongly discouraged where possible. Consequently, mobile health (mHealth) technology is taking its momentum to fulfil this gap. The purpose of this study is, therefore, to empirically investigate the moderating as well as the direct role of situational constraint and health consciousness in the unified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 75 publications
3
15
0
Order By: Relevance
“…Other studies, however, have corroborated our findings of the non-significant impact of performance expectancy and effort expectancy on the intention to adopt (51, 92). In addition, other previous findings have also illustrated that performance (93)(94)(95) and effort expectancy (96)(97)(98)(99) does not determine the intention to use. The reasons accounting for the nonsignificant performance expectancy and effort expectancy on the behavioral intention to adopt mobile health services could be due to first, the advanced technology savvy of citizens along with its long usage and hence they have become skilled at the use of technology related applications.…”
Section: Discussionmentioning
confidence: 79%
“…Other studies, however, have corroborated our findings of the non-significant impact of performance expectancy and effort expectancy on the intention to adopt (51, 92). In addition, other previous findings have also illustrated that performance (93)(94)(95) and effort expectancy (96)(97)(98)(99) does not determine the intention to use. The reasons accounting for the nonsignificant performance expectancy and effort expectancy on the behavioral intention to adopt mobile health services could be due to first, the advanced technology savvy of citizens along with its long usage and hence they have become skilled at the use of technology related applications.…”
Section: Discussionmentioning
confidence: 79%
“…25 Moreover, another study also identified a strong direct positive effect of both situational constraint and health consciousness on the behavioral intention to use mHealth technologies. 26 Second, there have been several papers showing empirical evidence to prove a rising demand for mHealth apps due to the pandemic situation. In the United States, patients with chronic health conditions such as cardiometabolic diseases, respiratory conditions, immune-related conditions, mental health, and obesity are more likely to use COVID-19 mHealth applications.…”
Section: The Roles Of Mhealth In Mitigating the Covid-19 Pandemic In The Developing Countriesmentioning
confidence: 99%
“…A cross-cultural (Bangladesh and China) study on mHealth investigated the relative importance of several factors influencing the intention and actual use of mHealth (Alam, Hu, Hoque, et al, 2020). However, while the COVID-19 outbreak was in full swing, Barua and Barua (2021) investigated the acceptance and usage behavior of mHealth care services. Beyond the behavioral study, Miah et al (2017) and Rahman et al (2021) have designed the mHealth prototype and evaluated it using a mixed-method approach.…”
Section: Introductionmentioning
confidence: 99%